فاعلية استخدام برنامج بواسطة الحاسب الالي على مستوي الاداء المهاري والمعرفي في كرة السلة لدي طالبات كلية التربية الرياضية بجامعة النجاح الوطنية - رفعت دويكات, بدر (Université de M'sila, 2013)
هدفت الدراسة الى التعرف على فاعلية استخدام برنامج بواسطة الحاسب الالي على مستوي الاداء المهاري والمعرفي في كرة السلة لدي طالبات كلية التربية الرياضية بجامعة النجاح الوطنية وتم اختيار العينة من الطالبات المسجلين بالكلية لمساق كرة السلة بالطريقة العمدية وبلغ عددهم 40 طالبة Abstract The Efficiency of Using Computerized Program on The Level of Technical and Cognitive Performance in Basketball amongst Female in The Faculty of Physical Education at An-najah National University The purpose of this study was to indentify the efficiency of using computerized program on the level of technical and cognitive performance in basketball amongst female in the faculty of physical education at An-najah National University. The sample of the study was consisted of (40) subjects, from basketball course, and they were divided equally for experimental and control groups. The Computerized Program(CP) applied on the experimental group for 8-weeks,three times a week, and 50minuts for each class, while the traditional program applied on the control group for the same duration. For analyzing data means, standard deviation, and t-test were used. The results of the study revealed a positive effect of using computerized program on the level of technical and cognitive performance in basketball .Also , the results indicated a significant differences in the level of technical and cognitive performance in basketball between experimental and control groups in favor of experimental group. Based on the findings of the study the researcher recommended to use educational technology in teaching practical courses for physical education students. Computerized Program, Technical, Cognitive, Basketball, Female, Physical Education.
Keywords: الحاسب الالي الاداء المهاري والمعرفي كرة السلة